2014
DOI: 10.3201/eid2011.131309
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Prevalence and Intensity of Foodborne Clonorchiasis, Hengxian County, China, 1989–2011

Abstract: During 1989–2011, three parasitic disease surveys were conducted in Hengxian County, China, where soil-transmitted helminthiases and foodborne clonorchiasis are endemic. We compared the data and found that the prevalence of helminthiases decreased and the prevalence and intensity of clonorchiasis increased over time, especially among men. Clonorchiasis control/intervention measures are urgently needed in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 8 publications
2
19
0
Order By: Relevance
“…In terms of gender, the positive rate in males was higher than that of females, and in terms of distribution among all age groups, the positive rate was higher in 50s and 60s. In the previous studies [19,24,25], males showed higher positive rate than females, showing the same results as this study. By age group, the results of previous studies which showed high positive rates in 40s and in 50s were considered to be similar to those of the 50s and 60s of this study.…”
Section: Nosupporting
confidence: 78%
See 1 more Smart Citation
“…In terms of gender, the positive rate in males was higher than that of females, and in terms of distribution among all age groups, the positive rate was higher in 50s and 60s. In the previous studies [19,24,25], males showed higher positive rate than females, showing the same results as this study. By age group, the results of previous studies which showed high positive rates in 40s and in 50s were considered to be similar to those of the 50s and 60s of this study.…”
Section: Nosupporting
confidence: 78%
“…Compared with the results of Lee et al's and Park et al's, the positive rate in this study shows a tendency to decrease. However, since 1989 in China, the rate of Clonorchis sinensis positive rate gradually increased to 46.5% in 2011 [19], showing a very high positive rate as compared with that of Korea. Despite the high economic growth, Korea and China have a dietary culture to enjoy freshwater fish, so Clonorchis sinensis infection is still regarded as a health problem which calls for a national strategy.…”
Section: Nomentioning
confidence: 99%
“…The people regularly consume raw fish even though the incidence of C . sinensis infection is high, and the infection rate has reached 53.6% (Qian et al 2014 ). In this investigation, C .…”
Section: Discussionmentioning
confidence: 99%
“…The sera from those infected with C. sinensis and control 1 were collected through a cross-sectional survey in Hengxian county, Guangxi Zhuang Autonomous Region, China, where C. sinensis infection is highly endemic [ 20 ]. One stool sample was collected from each participant.…”
Section: Methodsmentioning
confidence: 99%